Drug delivery systems in HIV pharmacotherapy: What has been done and the challenges standing ahead - Sosnik, Alejandro Dario (2009)
Worldwide, over 40 million people are infected with the Human Immunodeficiency Virus (HIV). The High Activity Antiretroviral Therapy (HAART) combines at least three antiretroviral (ARV) drugs and, for over a decade, has been used to extend the lifespan of the HIV-infected patients. Chronic intake of HAART is mandatory to control HIV infection. The frequent administration of several drugs in relatively high doses is a main cause of patient incompliance and a hurdle toward the fulfillment of the pharmacotherapy. High adherence to HAART does not lead to complete HIV virus elimination from the host. Intracellular and anatomical viral reservoirs are responsible for the perpetuation of the infection. Active transport mechanisms involving proteins of the ATP-binding cassette prevent the penetration of ARV drugs into the brain and may account for the limited bioavailability after oral administration. A new research that addresses from simple organoleptic or technological problems to more complex issues involving the targeting of specific tissues and organs has emerged. With the aim to reduce dosing frequency, to improve the compliance of the existing pharmacotherapy and to target viral reservoirs, the design of drug delivery systems is becoming complementary to new drug discovery. Based on to the common molecular features that characterize the different families of ARV drugs, the present review describes state-of-the-art ARV DDS and thoroughly discusses the challenges in the development of medicines with enhanced biopharmaceutical properties. In addition, a number of specific issues such as pediatric HAART, preventive pharmacotherapy and specific HIV-associated ethical issues are addressed in an integrative manner. Finally, the impact of such novel drug development on the Pharmaceutical Technology field is discussed.